PENERAPAN STRATEGI SQ3R DALAM PEMBELAJARAN MEMBACA KRITIS SASTRA (CERPEN) PADA SISWA MI KELAS LANJUT - Yaqin, M. Zubad Nurul (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2012)
Learning of reading literature (in this concerning short story) in formal education scope (as in Islamic elementary school, especially at advanced grade) wasn’t maximal yet. In objective condition, learning of reading short story at advanced grade, generally still definite in structure analyzing, didn’t administer in activities that able to train students in reading and appraising literature critically. Thus, learning activities by applying some strategy to achieve learning objectives need to do. Some strategy which can be used are SQ3R strategy.SQ3R strategy is one of strategy in learning of reading to help reader understand whole and detail about content of the text. By using SQ3R strategy, reader (students) will be faster to find mind idea in the text. Steps of SQ3R application are survey, question, read, recite, dan review. To achieve learning objectives maximally, that steps should be apllied systematically.